Development and preliminary evaluation of ilearnKAS: An animated video about kidney allocation to support transplant decision‐making. Issue 8 (1st July 2019) - Kayler, Liise K.; Keller, Maria M.; Crenesse‐Cozien, Natalia; Dolph, Beth; Cadzow, Renee; Feeley, Thomas H.
Abstract: Background: We aimed to develop and feasibility test an educational video culturally targeted to African American (AA) patients regarding kidney allocation. Methods: We iteratively refined an animated video for AAs with multiple stakeholder input and conducted a one‐group, pre–post study with 50 kidney transplant candidates to assess video feasibility and acceptability. A mixed population was chosen to obtain race‐specific acceptability data and efficacy estimates for a larger study. Results: Median participant age was 56 years, and 50% were AA. Comparing pre–post video scores, large knowledge effect sizes were found for the cohort ( r  = 0.7) and in the context of AA race ( r  = 0.8), low health literacy ( r  = 0.6), low educational achievement ( r  = 0.7), age >55 years ( r  = 0.6), dialysis vintage ≥1 year ( r  = 0.8), low income ( r  = 0.7) and low technology access ( r  = 0.8). Over 87% of participants provided positive ratings on each of the seven acceptability items. The frequency of positive responses increased pre–post video for kidney allocation understanding (78% vs 94%, P  = 0.008), decisional self‐efficacy (64% vs 88%, P  < 0.001) and belief in fairness (76% vs 90%, P  = 0.02). Conclusions: In collaboration with key stakeholders, a culturally targeted educational video was developed that was well received. Results are promising to impact kidney allocation knowledge among AA and non‐AA kidney transplant candidates.